Plate failure by bending following tibial fracture stabilisation in 10 cats. (28th July 2016) - Morris, A. P.; Anderson, A. A.; Barnes, D. M.; Bright, S. R.; Knudsen, C. S.; Lewis, D. D.; Pozzi, A.; Langley‐Hobbs, S. J.
Abstract : OBJECTIVE: To describe the clinical findings and management of tibial fractures in cats in which osteosynthesis failed due to plate bending. METHODS: Case records and radiographs of cat tibial fracture repairs from five referral centres were reviewed for signalment and to assess incidence of plate failure by bending. Cats that sustained plate bending following plate or plate‐rod fixation were reviewed for fracture configuration, repair method, initial postoperative and postfailure tibial alignment, revision treatment and outcome. RESULTS: The incidence of plate bending in cat fractures managed with plate and plate‐rod fixation in the four referral centres where the overall number could be established was 13% (8/60). In the 10 cats in which plates bent, initial fractures were generally oblique or spiral with mild comminution and located in the middle or distal third of the tibia. Mean time to implant failure was 24 days (range 2 to 56 days). Mean tibial valgus angle increased from 12·9° to 30·9° following bending of the plate. Short‐term outcome following revision surgery using orthogonal plating or stacked medial plates was favourable with improvement in tibial valgus in all five fractures with follow‐up data. CLINICAL SIGNIFICANCE: Plate bending following tibial fracture stabilisation in these 10 cats resulted in tibial valgus deformation. Consideration of plate and/or intramedullary rod selection and application should be given to avoid a plate strain environment that exceeds the yield point of the plate.